Impaired theta-gamma coupling in APP-deficient mice - Zhang, Xiaomin; Zhong, Weiwei; Brankačk, Jurij; Weyer, Sascha W.; Müller, Ulrike C.; Tort, Adriano B. L.; Draguhn, Andreas (Scientific reports, 2016)
Amyloid precursor protein (APP) is critically involved in the pathophysiology of Alzheimer’s disease, but its physiological functions remain elusive. Importantly, APP knockout (APP-KO) mice exhibit cognitive deficits, suggesting that APP plays a role at the neuronal network level. To investigate this possibility, we recorded local field potentials (LFPs) from the posterior parietal cortex, dorsal hippocampus and lateral prefrontal cortex of freely moving APP-KO mice. Spectral analyses showed that network oscillations within the theta- and gamma-frequency bands were not different between APP-KO and wild-type mice. Surprisingly, however, while gamma amplitude coupled to theta phase in all recorded regions of wild-type animals, in APP-KO mice theta-gamma coupling was strongly diminished in recordings from the parietal cortex and hippocampus, but not in LFPs recorded from the prefrontal cortex. Thus, lack of APP reduces oscillatory coupling in LFP recordings from specific brain regions, despite not affecting the amplitude of the oscillations. Together, our findings reveal reduced cross-frequency coupling as a functional marker of APP deficiency at the network level.
Richtiger Name vom 2. Autor: Weiwei Zhong
Gesehen am 12.02.2025